Systemic inflammatory response syndrome in a patient diagnosed with high grade inflammatory triple negative breast cancer: a case report of a potentially rare paraneoplastic syndrome. Issue 1 (December 2015) - Boshier, Piers; Sayers, Rosie; Hadjiminas, Dimitri; Mackworth-Young, Charles; Cleator, Susan; Leff, Daniel
Abstract Background Inflammatory breast cancer is a complex pathological entity associated with poor outcomes. This loco-regional disease is characterised by a rapid clinical course in the presence breast erythema and infiltration of dermal lymphatics by tumours cells. Herein we describe a case of inflammatory breast cancer with a rare presentation and disease course defined by a profound systemic inflammatory response in the absence of an infective cause. Case presentation The patient presented with pyrexia and malaise following a recent tissue diagnosis of inflammatory breast cancer. At the time of admission the patient demonstrated clinical features of the systemic inflammatory response syndrome (SIRS) in the presence of a negative septic screen. Her condition deteriorated despite systemic broad spectrum intravenous antibiotics and she underwent surgical debulking of a 180 × 135 × 100 mm (821 g) primary tumour composed of oedematous, friable and haemorrhagic tissue (pT4, N1a, M0; oestrogen/progesterone/HER-2 receptor negative). Following surgery, the clinical picture dramatically improved with cessation of SIRS and normalisation of inflammatory markers. After 4 weeks the patient required readmission to hospital due to recurrent SIRS and negative septic screen. The patient received treatment with systemic chemotherapy showing transient clinical improvement and suppression of SIRS. Despite on going chemotherapy, systemic antibiotics and a trial of steroid therapy the patient died 5 months after her initial presentation to hospital. At the time of death she demonstrated persistent SIRS with elevated inflammatory markers. Conclusion This is the first case report of inflammatory breath cancer associated with SIRS in the absence of clinically confirmed infection. Important learning points highlighted by this case are: (a) recognition of the diagnostic and therapeutic uncertainties that still exist in the context of inflammatory breast cancer; (b) appreciation of the potential paraneoplastic systemic inflammatory manifestations of this disease, and finally; (c) the importance a multidisciplinary and multimodal approach to treatment.